(untitled) (Global Journal of Human-Social Science, 2020)
Marriages sometimes come under attack due to various internal and extraneous factors that may include betrayal. Betrayal identified as one of the most destabilizing factor, comes as abuse of trust. The consequences of betrayal in marriages leave such marriages on the verge of collapse, and more often to divorce, separation, or abandonment. Women are mostly found vulnerable to betrayals in marriage relationships, although culpability could be with either the females or males. The effects of betrayal are traumatic. It leaves the offended injured and seeking a coping strategy. African literary texts have portrayed incidents and narratives that present women as victims, found to cope and adapt to the situation in different ways. So Long a Letter by Mariama Ba and Behind the Clouds by Ifeoma Okoye relay instances of betrayal, different responses, and coping strategies by the female protagonists. This essay makes a literary analysis of the incidents of marriage crises in the two texts highlighting the bitter experiences and reactions of individual victims. Using coping as a tool under the framework of Cognitive Psychological Adaptation, the essay examines the psychological effect of betrayal on the victims. A coping strategy is explored as a conscious effort devised by individual victims to construct, interpret, and resolve emotional and mental stress as a result of betrayal.